eGFR and chronic kidney disease stages among newly diagnosed asymptomatic hypertensives and diabetics seen in a tertiary health centre in Nigeria. (2014)
Objectives: Moderate to severe CKD, may be symptomless and therefore may be undetected if effort is not made to assess kidney function. The aim of this study was to determine the eGFR of asymptomatic newly diagnosed hypertensives and diabetics with a view to creating awareness for early screening, evalu ation and intervention especially in resource poor settings where kidney replacement therapy is prohibitive. Design, Setting, Participants: This is a retrospective study. Records of all hypertensive and diabetic patients referred to the medical clinic were included in the study for analysis. They were considered newly diagnosed if they were just being referred and were not on antihypertensive therapy or had been on therapy only in the last one month. The diagnosis of diabetes mellitus was made according to the guideline of the American Diabetes Association. We included in the analysis patients who had anthropometric measurements and serum creatinine from which we calculated the eGFR. Main Outcome Measures: Use of eGFR and CKD stage in asymptomatic newly diagnosed hypertensives and diabetics. Results: Six hundred and twenty-eight patients were included in the study. The mean age (SD) for men and women were 50.19 (12.41) and 48.63 (14.43) respectively. A total of 242 (38.5%) had stage CKD stages 3a, 3b and 4 with a predominance of females: 184 (29.6%) vs 58 (9.2%). There was an association between CKD stage, sex (x25135.56, P,.001) and age (x2530.83, P5.01). Conclusion: A substantial number of asymptomatic patients with hypertension and diabetes have CKD stages 3 and 4, associated with age and sex, but not with the BP stage. Without a proper evaluation, which includes determination of GFR, significant deterioration of kidney function may be missed and an appropriate intervention may not be instituted